On-chip power efficient MHz to GHz tunable Brillouin microwave photonic filters - Reena Parihar; Choon Kong Lai; Ziqian Zhang; Duk-Yong Choi; Stephen J. Madden; Benjamin J. Eggleton; Amol Choudhary; Moritz Merklein (APL Photonics)
Stimulated Brillouin scattering (SBS) offers optically tunable, narrowband gain and loss resonances, which makes it ideal for optical filtering and signal processing applications. However, broadband filters utilizing Brillouin scattering typically necessitate multiple pump sources or linear frequency modulated waveforms, which necessitate the use of overall high pump powers to achieve broadband and multi-band filter configurations. To overcome the trade-off between bandwidth and power consumption, we introduce an on-chip broadband bandpass filter scheme leveraging the SBS response and the concept of radio frequency interference. We present the MHz to GHz reconfigurable microwave photonic filters on a chip. The bandwidth is tunable from 30 MHz to 1.2 GHz at a total pump power of only 15 dBm, corresponding to a figure of merit (maximum bandwidth/pump power) improvement of a factor of 25 compared to previously reported work. Furthermore, the filter exhibits frequency tuning capabilities ranging from 10 to 40 GHz (X to Ka-band) and can be configured from single- to multi-bandpass filter responses and switched from bandpass to bandstop.